Analisa Penerapan Sistem Merit di Pemerintah Kota Mataram dari Perspektif Gender - Hidayat, Rahmad; Salmin, Salmin; Mustamin, Mustamin; Hadi, Ayatullah (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2024)
Human resources (apparatus) are the basis of the bureaucratic reform movement. Human resources are one aspect of achieving the goals of government organizations, namely providing optimal public services. Therefore, it is necessary to implement a merit system to obtain human resources, in this case specifically the best State Civil Apparatus (ASN) who do not consider male or female gender, including in the process of filling pratama high leadership positions (JPT) in scope of the Mataram City Government. This research aims to describe the implementation of the merit system in the Mataram City government from a gender aspect. This research uses a qualitative approach with data collection methods consisting of in-depth interviews and document review. Data analysis uses qualitative data analysis techniques. The validity of the data was tested using triangulation techniques. Research provides an illustration that the Mataram City government has basically implemented a merit system in ASN management. When filling out the JPT, preparation, implementation and evaluation stages have been carried out in accordance with the provisions. Basically, the number of female ASNs in the city of Mataram is more than male. Likewise, the educational level of female ASN is better than that of men. However, if we look at it in terms of rank and class, the number of men is increasing, this will make the opportunity for men to occupy top positions in the bureaucracy greater. The Mataram city government consistently provides opportunities for women at the rate of 10 percent and hopes that in the future this will be further increased.